A comparison of recommendations for pharmacologic thromboembolism prophylaxis after caesarean delivery from three major guidelines. (5th October 2015) - Palmerola, KL; D'Alton, ME; Brock, CO; Friedman, AM
Abstract : Objective: Guidelines for pharmacologic obstetric venous thromboembolism (VTE) prophylaxis from the American Congress of Obstetricians (ACOG), the Royal College of Obstetricians and Gynaecologists (RCOG), and the American College of Chest Physicians (Chest) vary significantly. The objective of this study was to determine the practical implications of these recommendations in terms of prophylaxis rates for a tertiary obstetric population. Study design: Cross‐sectional. Setting: Tertiary referral hospital. Population: Patients post‐operative day 1 after caesarean delivery. Methods: This cross‐sectional study evaluated rates of pharmacologic prophylaxis for women based on RCOG, ACOG, and Chest recommendations. Medical, obstetric, and demographic risk factors for thromboembolism were reviewed for individual patients. Rates of prophylaxis based on each of the guidelines with 95% confidence intervals were calculated. Outcome measure: Recommended pharmacologic prophylaxis. Results: About 293 patients were included in the analysis. Under RCOG guidelines, 85.0% of patients would receive post‐caesarean pharmacologic prophylaxis [95% confidence interval (CI) 80.5–88.6%] compared with 1.0% of patients under ACOG guidelines (95% CI 0.3–3.0%) and 34.8% of patients under Chest guidelines (95% CI 29.6–40.4%). Caesarean during labour, obesity, advanced maternal age, pre‐eclampsia, and multiple gestation were among the most commonrisk factors. Conclusion: Recommended prophylaxis differed significantly. Under ACOG recommendations a small minority of patients would receive prophylaxis, whereas under RCOG recommendations a large majority of patients would receive low‐molecular‐weight heparin. Given the large differences in prophylaxis rates for post‐caesarean thromboprophylaxis based on different guidelines, further research is urgently needed to compare the risks and benefits of recommendations. Tweetable Abstract: Recommendations from major society guidelines for post‐caesarean thromboprophylaxis differ greatly. Tweetable Abstract: Recommendations from major society guidelines for post‐caesarean thromboprophylaxis differ greatly. This article includes Author Insights, a video abstract available athttps://vimeo.com/rcog/authorinsights13706